Fortalecimento da agricultura familiar: caracterização físico-química, nutricional e sensorial de cultivares de morango - Nunes, Graziela (2019)
Strawberry cultivation is an agricultural practice exploited mainly by family farming, due to the economic profitability of the crop. However, the choice of the strawberry cultivar to be produced is one of the greatest difficulties faced by producers during the harvests. That is because the productivity and quality of the strawberry may vary according to your genetic profile. Thus, interdisciplinary research involving the areas of Agrarian Sciences, such as Agronomy, Food Engineering and Food Technology, and Health Sciences, such as Nutrition, may be an alternative to identify the strawberry genotypes that are more favorable for production and consumption . The present study was carried out in three stages, the first one was composed of a review of the literature on the strawberry crop. The second stage aimed to evaluate the sensory, physical-chemical and nutritional characteristics of different strawberry cultivars, in order to identify the genotype (s) with the best characteristics for commercialization and human consumption. In the third stage, an experience report was elaborated in a training for family farmers. The strawberry production, the physicochemical, nutritional and sensorial composition of the fruit and its potential consumption effects on human health were discussed in the review study. In the second stage, the cultivars Aromas, Camarosa, Camino Real, Dover, Sweet Charlie and Tudla were characterized as to their sensorial, physical-chemical and nutritional aspects. The training (step 3) aimed to train strawberry producers to process and preserve the fruit in the post-harvest period. As a pedagogical strategy to fix and take advantage of the information contemplated in the training, a cookbook was prepared with all the contents addressed. It was possible to verify that the physical-chemical, nutritional and sensorial characteristics of the strawberry can be directly affected by the cultivation system, environmental conditions, genotype, methods of preservation and storage. In addition, strawberry is considered a functional food due to the remarkable bioactivity of its compounds in reducing the risk of cardiovascular diseases, obesity, diabetes mellitus, metabolic syndrome and cancer. Among the genotypes evaluated in this study, Camarosa, Camino Real, Dover and Tudla present greater acceptability among consumers, whereas for Aromas and Sweet Charlie the reverse was observed. Camarosa, Sweet Charlie and Tudla presented better physical-chemical characteristics for human consumption, while the reverse was observed in Aromas, Camino Real and Dover. The concentration of nutrients was higher in the cultivars Camarosa, Dover and Tudla, while Aromas, Camino Real and Sweet Charlie were the less favorable cultivars in this respect. The presentation of the theoretical content during the training stimulated the raising of doubts by the participants, which is essential in the process of learning and assimilation of information. In addition, the exchange of mutual information between the participants and the executing team during the preparation of the recipes provided the improvement of the pre-existing practical knowledge of the farmers. In general, it is concluded that strawberry is considered a healthy food choice due to its preventive and therapeutic potential in several pathologies. Among the evaluated genotypes, Camarosa and Tudla are more favorable for human consumption, considering the sensorial, nutritional and physico-chemical characteristics. The activities developed in the training addressed the main difficulties of the family farmers in the conservation and use of strawberries in the post-harvest period. In addition, the educational material is a fundamental strategy for the autonomy of the producers in the continuity of the activities in their properties. The interdisciplinary perspective of this research allows an approximation of the scientific community to the problems experienced by family farmers and, thus, promoting community development.